INTERNAL AUDIT QUALITY AND PERFORMANCE OF PUBLIC TERTIARY INSTITUTIONS IN OSUN STATE, NIGERIA - Khadijah Adeola IDOWU; IBRAHIM Jimoh (Malete Journal of Accounting and Finance)
Despite the presence of internal audit mechanism in most public tertiary institutions, evidence has shown that most of them have experienced audit failure in recent years with consequential effect on the effectiveness and efficiency in quality of service delivery, financial control and performance. In view of this, the study examined the impact of internal audit quality on performance of public tertiary institutions in Osun State, Nigeria. Primary data was obtained through the administration of structured questionnaire to 72 respondents out of total population of 151 comprising staff of internal audit and bursary departments in three state-owned tertiary institutions in Osun State. Data obtained was analyzed using Correlation Analysis and OLS - Multiple Regression technique. The results show that there is a significant relationship between internal audit quality and performance of Osun state-owned tertiary institutions as confirmed with F (3, 68) = 52.96; P< 0.05). The study concluded that internal audit quality is a veritable tool for promoting performance in terms of efficiency, effectiveness, economy, and quality of service delivery of state-owned tertiary institutions. This study therefore, recommended among others that internal auditor competence and independence should be given more attention and mechanism through which these qualities can be employed and sustained for better internal audit service delivery to enhance performance of public tertiary institutions.